Qualitative and Quantitative Analysis on Flavonoid Distribution in Different Floral Parts of 42 Hemerocallis Accessions - Li, Sen; Cui, Huliang; Wang, Jinyao; Hou, Feifan; Xiong, Xiong; Kang, Xiuping; Xing, Guoming (Frontiers in Plant Science, 2021)
The Hemerocallis accessions is widely consumed as nutritious vegetable and traditional medicine in eastern Asia and used as an ornamental flower worldwide. Compared with most other horticultural products, its flower is richer in polyphenols, flavonoids, carotenoids, and anthocyanins. Therefore, the flower has strong antioxidant activity that inhibits cancer cell proliferation, which could used for health and pharmaceutical purposes. The flavonoids composition and distribution in the flowers, and the content varied between different accssions is still unclear. In this context, eight flavonols, two flavones, and two anthocyanins were determined in Hemerocallis flower by high-performance liquid chromatography (HPLC) coupled with photodiode array and mass spectrometric detectors. Rutin was the most abundant flavonols and cyanidin 3,5-glucoside and cyanidin 3-rutinoside were the major anthocyanins in Hemerocallis tepals, resulting in flower petal coloration, and their content in the petal was higher than that of the sepal. Hierarchical cluster analysis grouped the 42 accessions into four groups, and they were significantly different (p < 0.05) from each other in the ten significant compounds by One-way ANOVA. Overall, the qualitative and quantitative analysis of flavonoid constituents in six floral parts of 42 Hemerocallis accessions were elucidated, which could be helpful for the food and pharmaceutical industries, and lay the foundation for the Hemerocallis flower color research.